TEACHING WRITING NARRATIVE TEXT BY USING WEBTOON DIGITAL COMIC TO SENIOR HIGH SCHOOL STUDENTS - Raulan Raulan; Sitti Fatimah (Universitas Negeri Padang, 2018)
Writing narrative text might be an unattractive activity for high school students. It is considered be a hard work, students find difficulty in arranging the sentences because lack of literacy and ideas. Here, author suggests the use of Webtoon digital comic to help teacher in teaching writing narrative text in order help students to organize and develop ideas. In process of writing narrative text, author uses five phases: pre-writing, drafting, revising, editing, and publishing, where the activity in one of the phases is read Webtoon digital comic as an activity to enhance students in generating ideas. This activity does not include any papers at all since the activity is done by using Smartphone and laptop connected with internet. By integrating the use of ICT in this learning activity, it is hoped teacher and students might increase the awareness of ICT implementation to facilitate the learning activity.